Respuesta :
(x−4)(x^2+5x+6)
=(x+−4)(x^2+5x+6)
=(x)(x^2)+(x)(5x)+(x)(6)+(−4)(x^2)+(−4)(5x)+(−4)(6)
=x3+5x^2+6x−4x^2−20x−24
=x^3+x^2−14x−24
=(x+−4)(x^2+5x+6)
=(x)(x^2)+(x)(5x)+(x)(6)+(−4)(x^2)+(−4)(5x)+(−4)(6)
=x3+5x^2+6x−4x^2−20x−24
=x^3+x^2−14x−24
Answer:
x³ + x² - 14x - 24.
Step-by-step explanation:
Given : (x – 4)(x² + 5x + 6).
To find : multiply.
Solution : We have given that (x – 4)(x² + 5x + 6).
Distribute the x over (x² + 5x + 6) and 4 ((x² + 5x + 6).
x (x² + 5x + 6) - 4(x² + 5x + 6).
(x³ + 5x² +6x ) -4x² - 20x - 24).
Combine like terms
x³ + 5x² - 4x² -20x +6x -24.
x³ + x² - 14x - 24.
Therefore, x³ + x² - 14x - 24.